Проблема формирования нравственного воспитания молодежи в высшем учебном заведениb - Разумова, Л.П. (My University, 2016)
In article the main problems of formation of moral education of youth in a higher educational institution are considered. Being guided by the theoretical analysis of scientific and pedagogical works on a problem of formation of moral education of students, the main reasons interfering formation of moral education are allocated
Keywords: moral; formation of moral education psychology and pedagogical conditions; higher educational institution